Business customers' readiness to adopt manufacturer's new services. Issue 1 (20th November 2017) - Vaittinen, Eija; Martinsuo, Miia; Ortt, Roland
Abstract : Purpose: For successful servitization, manufacturing firms must understand how their customers adopt new services. The purpose of this paper is to explore customers' readiness for a manufacturer's new services to complement its goods. The goal is to increase knowledge of the aspects that manufacturers should consider when bringing new kinds of services to market. Design/methodology/approach: A qualitative case study design is used to analyze readiness for services and interest in service adoption in three customer firms of a manufacturer. The interview data were collected from 14 persons at customer sites and were content analyzed. Findings: The results show that readiness – a concept that is often used in the field of technology – is relevant also for the service adoption process. In a business-to-business context, readiness for service adoption concerns the individual and organizational levels, and hence a new dimension of organizational culture and habits had to be added to the concept that originally focuses on individuals. People consider different factors when making consecutive decisions during the service adoption process and these factors can vary even within a company. The cornerstone for new service adoption is the customer firm's actual need for the service. Originality/value: The results offer new knowledge about service adoption in a business-to-business context by taking a customer firm's perspective. They, thus, complement previous studies on the supplier perspective of servitization and service adoption in consumer business. The contributions help manufacturers focus their efforts when bringing new services to market.